Book Review: Integrating Education, Health, and Social Services in Rural Communities: Service Integration Through the Rural Prism - Carol E. Mertens (Journal of Research in Rural Education, 1995)
The integration of education, health, and social service to enhance efficiency and effectiveness is once again being embraced by policy makers and those involved in the delivery of human services. The fragmentation of the human service system has created a lack of coordination of services and artificial, but real, barriers for the individuals the system is designed to serve.